MODEL DAKWAH KULURAL ZASTROUW AL-NGATAWI - Suciatie Sifa Endah Masdini; Dewi Anggraeni (Mozaic : Islam Nusantara, 2020)
Zastrow Al-Ngatawi as the subject of this research has done something similar to Wali Songo, but the scope of activities carried out by Zastrow Al-Ngatawi is more simple. The thing he did was one of the glory in Da’wah activities. This research is qualitative descriptive. The subject in this study was Zastrouw Al-Ngatawi. Data collection methods used in this study were observation, interviews, and documentation. For analysis using Miles and Huberman's interactive analysis theory which includes data reduction (data reduction), presenting data (data display), and making conclusions or verification (conclusion drawing).